Analisis Risiko dan Return Menggunakan Metode CAPM Terhadap Keputusan Investasi pada Indeks LQ45 Periode 2018-2022 - Lailatus Sa’adah; Taufik Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze stock returns and risks, as well as grouping efficient and inefficient stocks to make investment decisions using the Capital Asset Pricing Model (CAPM) model. This type of research is descriptive research with a quantitative approach. The samples used were companies in the LQ45 index in the infrastructure and transportation sectors during the 2018-2022 period using the purposive sampling method so that a total sample of 2 companies was obtained. Calculations using the CAPM model result in 1 efficient company and 1 inefficient company. Shares of PT. XL Axiata Tbk. is an undervalued stock, because the value of the individual rate of return (Ri) is higher at 0.00152 or 0.15%, with the resulting investment decision for stocks in the efficient category is to consider buying these shares at the lowest price today before experiencing an increase in the future. While the shares of PT. Telkom Indonesia Tbk. is an overvalued stock, because the value of the individual rate of return (Ri) is lower at 0.00190 or 0.19% of the expected rate of return E(Ri) which is 0.00223 or 0.22%, the resulting investment decision for stocks with inefficient category is to sell the shares at the highest price now and before experiencing a price decline in the future.